Generalization of threats attributed to large carnivores in areas of high human–wildlife conflict. Issue 5 (4th August 2022) - Ashish, Kumar; Ramesh, Tharmalingam; Kalle, Riddhika; Arumugam, Rathinasamy
Abstract: Fear‐induced generalization of threats to noninimical stimuli is a behavioral tendency of humans to minimize exposure to potential threats. In human–carnivore conflict zones, people often generalize their fear of predation by obligate carnivores to nonobligate carnivores despite differences in species' predation rates. We investigated the effect of a perceived threat of large obligate carnivores to livestock on tolerance and perception of striped hyena ( Hyaena hyaena ) in an area of high human–carnivore conflict. We surveyed 197 households through asemistructured questionnaire to determine people's perception and tolerance of striped hyenas in Sathyamangalam and Mudumalai Tiger Reserves after identification of the current distribution range of hyena determined through camera trap and sign surveys. Through the random forest algorithm, we modeled the level of tolerance of striped hyena as a function of loss of livestock to predation and from disease, the perceived threat of predation by hyena, and other socioeconomic attributes. Animal husbandry was a major source of income but was severely affected by livestock loss due to predation and disease. Sixty‐nine percent of people were uncertain about predatory behavior of hyena; out of that, 23% reported a negative conservation attitude. Only 6 instances of hyena depredation on livestock and 2 on dogs were reported. Our model confirmed that economic instability associated with increased loss to predation and disease, livestock dependency, and a decrease in family annual income negatively affected people's tolerance of hyena. Perceptual uncertainty related to predatory behavior of hyena also negatively affected people's tolerance. In our study area, economic instability and perceptual uncertainty led to generalization of fear of large carnivores to a nonobligate predator. Such generalization may affect the attitude of people toward many other species. Understanding the role of economic instability and perceptual uncertainty should facilitate conservation of species, such as the hyena, that are vulnerable to false generalization. Abstract : Generalización de las Amenazas Atribuidas a los Grandes Carnívoros en las Áreas con un Elevado Conflicto Humano‐Fauna Resumen: La generalización de las amenazas inducidas por el miedo a los estímulos no desfavorables es una tendencia del comportamiento humano para minimizar la exposición ante las amenazas potenciales. En las zonas de conflicto humano‐carnívoros, las personas transfieren con frecuencia su miedo a los carnívoros obligados hacia los no obligados a pesar de las diferencias en las tasas de depredación de las espcies. Investigamos el efecto de la amenaza percibida que representan los grandes carnívoros obligados para el ganado sobre la tolerancia a y la percepción de la hiena rayada ( Hyaena hyaena ) en un área con un conflicto elevado entre humanos y carnívoros. Encuestamos a 197 hogares con un cuestionario semiestructurado para determinar la percepción y tolerancia que tienen las personas hacia la hiena rayada en las reservas de tigres de Satayamangalam y Mudumalai después de identificar la distribución actual de la hiena mediante cámaras trampa y censos de indicios. Modelamos el nivel de tolerancia a la hiena rayada con el algoritmo de bosque aleatorio como función de la pérdida de ganado por depredación o enfermedad, la amenaza percibida de la hiena como depredador y otros atributos socioeconómicos. La crianza de animales fue una gran fuente de ingresos aunque con severas afectaciones por la pérdida de ganado por depredación o enfermedad. El 69% de las personas tenían incertidumbre acerca del comportamiento de depredación de la hiena; de ese porcentaje, el 23% reportó una actitud negativa de conservación. En cuanto a las hienas, sólo se reportaron seis instancias de depredación de ganado y dos de perros. Nuestro modelo confirmó que la inestabilidad económica asociada con el incremento en las pérdidas por depredación y enfermedad, la dependencia por el ganado y una reducción en el ingreso anual familiar afectó negativamente la tolerancia que tienen las personas hacia las hienas. La incertidumbre percibida relacionada con el comportamiento de depredación de las hienas también afectó negativamente la tolerancia de las personas. La inestabilidad económica y la incertidumbre percibida derivaron en una transferencia del miedo a los grandes carnívoros hacia los depredadores no obligados en nuestra área de estudio. Dicha transferencia puede afectar la actitud de las personas hacia muchas otras especies. El conocimiento sobre el papel que tiene la inestabilidad económica y la incertidumbre percibida debería facilitar la conservación de especies que son vulnerables a las falsas generalizaciones, como es el caso de la hiena. 【摘要】: 人类在恐惧的诱发下, 具有泛化非有害刺激造成的威胁的行为倾向, 即要尽量减少暴露在潜在威胁中的机会。在人类与食肉动物冲突的地区, 尽管每个物种的捕食率不同, 但人们经常将对专性食肉动物捕食的恐惧泛化到非专性食肉动物之上。本研究调查了在一个人类与食肉动物高度冲突的地区, 人们对于大型专性食肉动物捕食家畜的感知威胁导致的对条纹鬣狗( Hyaena hyaena )容忍度和认知的影响。我们通过半结构化问卷调查了197个家庭, 以确定人们对印度Satayamangalam和Mudumalai老虎保护区中条纹鬣狗的认知和容忍度, 此前我们已通过红外相机和标志调查确定了鬣狗当前的分布范围。我们通过随机森林算法, 将对条纹鬣狗的容忍度作为家畜因捕食和疾病造成的损失、感知到的鬣狗捕食威胁, 以及其他社会经济属性的函数进行了建模。畜牧业是这些家庭主要的收入来源, 但由于捕食和疾病造成的家畜损失严重影响了收入。我们发现, 69%的受访者不能确定鬣狗的捕食行为;其中23%的人报告了消极的保护态度。然而, 受访者只报告了6起鬣狗攻击家畜和2起攻击狗的事件。我们的模型证实, 与捕食和疾病损失增加有关的经济不稳定性、对家畜的依赖, 以及家庭年收入的减少, 对于人们是否容忍鬣狗产生了负面影响。与鬣狗捕食行为有关的感知不确定性也对容忍度存在负面影响。在我们的研究地区, 经济不稳定性和感知不确定性导致人们对大型食肉动物的恐惧被泛化到非专性捕食者之中。这种泛化可能影响人们对许多其他物种的态度。理解经济不稳定性和感知不确定性的作用, 有助于保护那些容易被错误泛化的物种(如鬣狗)。